Analytical Model for Detection the Tilt in Originally Oil Water Contacts - Abdulwahid Al-Sudani, Jalal (Iraqi Journal of Chemical and Petroleum Engineering, 2014)
Many carbonate reservoirs in the world show a tilted in originally oil-water contact (OOWC) which requires a special consideration in the selection of the capillary pressure curves and an understanding of reservoir fluids distribution while initializing the reservoir simulation models.An analytical model for predicting the capillary pressure across the interface that separates two immiscible fluids was derived from reservoir pressure transient analysis. The model reflected the entire interaction between the reservoir-aquifer fluids and rock properties measured under downhole reservoir conditions.This model retained the natural coupling of oil reservoirs with the aquifer zone and treated them as an explicit-region composite system; thus the exact solutions of diffusivity equation could be used explicitly for each region. The reservoir-aquifer zones were linked by a capillary transition zone that reflected the pressure difference across the free water level.The principle of superposition theorem was applied to perform this link across the free water level to estimate the reflected aquifer pressure drop behavior that holds the fluid contacts in their equilibrium positions.The results of originally oil water contact positions generated by the proposed model were compared with data obtained from a carbonate oil field; the results given by the model showed full agreement with the actual field data.